Analysing the Workforce Composition of Agrarian Sector: A Comparison between Uttar Pradesh and Tamil Nadu - Alka Verma; Seema Tiwari (National Geographical Journal of India, 2022)
Agriculture is the foundational domain of Indian economy and it still continues to engage major proportion of the country’s workforce. The paper attempts to study the changes in agrarian workforce of two states namely Uttar Pradesh and Tamil Nadu over a decade. The study makes use of evidence from two census years’ data namely 2001 and 2011. This paper attempts to study the characteristics of agricultural workforce of both the states with the application of analytical, interpretative and graphical techniques. The study makes use of comparative analysis and tries to find out the differences between agrarian workers of Uttar Pradesh, predominantly an agricultural state and Tamil Nadu, an industrial state. The findings of the study are quite striking, as Tamil Nadu shows a positive growth in conditions of agrarian workers while Uttar Pradesh in spite of being an agrarian state shows negative growth in conditions of peasants.